The Impact of Leverage, Wealth, and Audit Management on Local Government Performance - Amalia, Dewi; Ariani, Windy Novita; Suripto, Suripto; Azizah, Zahra Fitri (Universitas Trunojoyo Madura, 2024)
This research examines the influence of government size, leverage, audit findings, audit follow-up recommendations, wealth, and capital expenditure on local government performance. This research using quantitative method with data from 154 local governments, with panel data regression to identify significant relationships. Researchers present a new analysis of the relationship between wealth, audit recommendations, and leverage on local government performance in Sumatra, Indonesia. The findings show that leverage has a significant negative impact on government performance, while variables such as government size, audit findings, follow-up recommendations, wealth, and capital expenditure do not show significant effect. This suggests that local governments with higher levels of debt experience difficulties in maintaining effective performance due to financial constraints and debt repayment burdens. Additionally, larger government size is not necessarily associated with better performance, perhaps due to the challenges associated with managing a larger bureaucracy. This study provides new insights into public sector financial management and contributes to the existing literature on local government performance, with potential implications for policy reform and management strategies.